Analysis and Comparison of Methods Evaluation Process Multifactor Simple Additive Weighting Method In Tilawatil Musabaqah Quran (MTQ) North Sumatra Province - Heriyanto, Heriyanto; Manahan, Olven (Journal of Computer Networks, Architecture and High Performance Computing, 2020)
The purpose of holding an MTQ is Essentially to broadcast the Koran while looking for the bestto represent the MTQ at the next level. But the point is the greatness of newspapers. With that symbol, itIS ALSO DEMANDED that a person is not only good at reading and writing, but far more important isunderstanding the content of the newspaper itself. The goal is not only for of participants (who take partin the competition) but Also (and this is more important) for the listener. Decision Support System (DSS)is used as an alternative to application in the selection of MusabaqahTilawatil Quran (MTQ) in NorthSumatraProvince by using the multifactor Evaluation Process Method and the Simple AdditiveWeighting Method. In the MFEP and SAW methods decision making is done by giving Subjective andobjective considerations Considered to factors that are important. Reviews These considerations are in the form of weighting the multifactor Involved and are Considered important. With this Analysis and Comparison, it is expected to be Able to find a more suitable method and Be Able to help as a jury assistant to take a decision on the contestants and can help solve the problems in the MusabaqahTilawatil Quran (MTQ) Selection in North Sumatra Province properly.